ORGANIZING AND CONDUCTING EXTRACURRICULAR ACTIVITIES IN A FOREIGN LANGUAGE TEACHING - Narziyeva Inobat Zoirovna (Лучшие интеллектуальные исследования, 2023)
Abstract: This article provides a detailed overview of the extracurricular work in foreign language teaching. In addition, it provides examples and clear analysis of how important it is to apply this method to life as well as to teaching process. Extracurricular work in foreign languages are essential in the education process. They complement foreign language classes, expanding and deepening students' knowledge and skills. Most importantly, students' interest in foreign languages will increase. Organizing and conducting extracurricular activities in a foreign language can help improve the educational process.